Design, synthesis, and carbonic anhydrase inhibition activities of Schiff bases incorporating benzenesulfonamide scaffold: Molecular docking application - Adel S. El-Azab; Alaa A.-M; Silvia Bua; Alessio Nocentini; Ahmed H. Bakheit; Hamad M. Alkahtani; Mohamed M. Hefnawy; Claudiu T. Supuran (Elsevier, 2023)
In this study, The inhibitory actions of human carbonic anhydrase (CA, EC 4.2.1.1) (hCA) isoforms I, II, IX, and XII are being examined using recently synthesized substituted hydroxyl Schiff derivatives based on the quinazoline scaffold 4-22. Quinazolines 2, 3, 4, 5, 7, 10, 15, and 18 reduce the activity of hCA I isoform effectively to a Ki of 87.6-692.3 nM, which is nearly equivalent to or more potent than that of the standard drug AAZ (Ki, 250.0 nM). Similarly, quinazolines 2, 3, and 5 and quinazoline 14 effectively decrease the inhibitory activity of the hCA II isoform to a KI of 16.9-29.7 nM, comparable to that of AAZ (Ki, 12.0 nM). The hCA IX isoform activity is substantially diminished by quinazolines 2-12 and 14-21 (Ki, 8.9-88.3 nM against AAZ (Ki, 25.0 nM). Further, the activity of the hCA XII isoform is markedly inhibited by the quinazolines 3, 5, 7, 14, and 16 (Ki, 5.4-19.5 nM). Significant selectivity levels are demonstrated for inhibiting tumour-associated isoforms hCA IX over hCAI, for sulfonamide derivatives 6-15 (SI; 10.68-186.29), and 17-22 (SI; 12.52-57.65) compared to AAZ (SI; 10.0). Sulfonamide derivatives 4-22 (SI; 0.50-20.77) demonstrated a unique selectivity in the concurrent inhibition of hCA IX over hCA II compared to AAZ (SI; 0.48). Simultaneously, benzenesulfonamide derivative 14 revealed excellent selectivity for inhibiting hCA XII over hCA I (SI; 60.35), whereas compounds 5-8, 12-14, 16, and 18-22 demonstrated remarkable selectivity for hCA XII inhibitory activity over hCA II (SI; 2.09-7.27) compared to AAZ (SI; 43.86 and 2.10, respectively). Molecular docking studies additionally support 8 to hCA IX and XII binding, thus indicating its potential as a lead compound for inhibitor development.